Corporate sustainability assessment in financing the extractive sector - Weber, Olaf; Banks, Yolanda (Journal of Sustainable Finance & InvestmentJournal of Sustainable Finance & Investment, 2012)
The role of the extractive sector with regard to sustainable development is discussed controversially. On the one hand, it is argued that the sector's adverse sustainability impacts outweigh its social and economic benefits and therefore the concept of socially responsible investment (SRI) is not applicable to the extractive sector. On the other hand, it is argued that the products from the extractive industries are essential for the world's economy, that the sector contributes to poverty reduction and to economic development, and creates revenues for governments. Based on this discussion, we analysed whether there is a relation between sustainability performance and financial performance in the extractive industry sector, whether Canadian companies from the extractive sector perform differently than companies from other regions, and how a sustainability assessment can be integrated into project finance. Our results suggest that Canadian companies from the extractive sector perform well with respect to their financial return, but that they do not outperform their global peers regarding sustainability. Furthermore, we did not find a strong correlation between sustainability performance and financial performance. Thus, we conclude that socially responsible investors have to pick those companies that perform well regarding both sustainability and financial returns.